2002
DOI: 10.4269/ajtmh.2002.67.349
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the magnitude of fatal Rocky Mountain spotted fever in the United States: comparison of two national data sources.

Abstract: Abstract. To assess the magnitude of fatal Rocky Mountain spotted fever (RMSF) and to evaluate the completeness of national surveillance for this occurrence from 1983 through 1998, two independent sources of RMSF mortality data were analyzed using a capture-recapture method. Two hundred twenty-four deaths reported through RMSF case report forms (CRFs) were compared with 304 RMSF-associated deaths recorded in the United States multiple cause-of-death (MCD) database. Demographic, geographic, seasonal, and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…Among the casepatients from the United States, no significant differences were noted between the percentages of male (54%) and nonwhite (18%) individuals evaluated in our study and the corresponding percentages (59% and 18%, respectively) among RMSF deaths documented by CRF surveillance data during 1983-2007. 22, 23 However, our analysis included significantly more United States case-patients 10 years of age (40% versus 15%, P value 0.0001), and significantly fewer casepatients 40 years of age (29% versus 63%, P value 0.0001) when compared with the ages of United States RMSF decedents reported to CDC during the same approximate period.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Among the casepatients from the United States, no significant differences were noted between the percentages of male (54%) and nonwhite (18%) individuals evaluated in our study and the corresponding percentages (59% and 18%, respectively) among RMSF deaths documented by CRF surveillance data during 1983-2007. 22, 23 However, our analysis included significantly more United States case-patients 10 years of age (40% versus 15%, P value 0.0001), and significantly fewer casepatients 40 years of age (29% versus 63%, P value 0.0001) when compared with the ages of United States RMSF decedents reported to CDC during the same approximate period.…”
Section: Resultsmentioning
confidence: 94%
“…In fact, among United States case-patients, significantly more young children and fewer persons 40 were represented when compared with national surveillance statistics for fatal RMSF in the United States during 1983-2007. 23,24 Chronic alcohol abuse is another risk factor that may increase the severity of RMSF, 34 in a manner similar to its demonstrated association with cases of fatal Mediterranean spotted fever, caused by the closely related bacterium, Rickettsia conorii. 46,47 Although information regarding alcohol use was not available for most case-patients in our series, it is important to note that the single Hlp-associated death occurred in a patient with alcohol dependency.…”
Section: 41mentioning
confidence: 90%
See 2 more Smart Citations
“…Other reports have demonstrated that fatal RMSF cases are underreported, 7,8 and this type of co-infection may demonstrate another reason why a fatal case would go undiagnosed. Serologic results are not likely to be positive for a patient who dies on the fifth day of symptoms, and a specialized diagnostic test such as PCR may not be pursued in cases that have positive cultures for another pathogen.…”
Section: Discussionmentioning
confidence: 91%